Program Evaluation and Assessment of Vital Sign Measurement at Student-Run Free Ophthalmology Clinics - Thakur, Shambhawi; Schmidt, Christian; Sharma, Rohan; Sa, Lydia; Sheehan, Brynn; McCole, Shannon; Leader, Alexandra (Journal of Student-Run Clinics, 2022)
Background: Uninsured patients (8.6% of the United States population) are more likely to have poorly controlled diabetes and hypertension, which can lead to altered vision or even blindness. Checking vital signs regularly is important in monitoring chronic diseases to prevent poorer health outcomes, especially in populations with limited access to care. HOPES (Health Outreach Partnership of Eastern Virginia Medical School Students) and CCE (Clínica Comunitaria Esperanza) are student-run free clinics that serve the uninsured population of Hampton Roads, Virginia. This study describes the services offered and examines trends in measuring vital signs at HOPES and CCE Ophthalmology Clinics to evaluate clinical operations and areas for improvement. Methods: A retrospective chart review of 347 HOPES and CCE Ophthalmology appointments from January 2015 to June 2021 explored patient demographics, vital sign measurement, reason for visit, diagnoses, and services provided. Chi-square tests were utilized to compare the measurement of vital signs between the two clinics. Results: 179 appointments met inclusion criteria. Of the 39 different reasons for visit, the most common were blurry vision, diabetic eye exams, floaters, and systemic hypertension. Of the 63 distinct diagnoses made, the most common were cataracts, diabetes with or without retinopathy, and presbyopia. A total of 175 services were provided, including 61 custom frames and glasses, 48 prescriptions for glasses, 54 medications, and 26 referrals to other providers. Vital signs were obtained during 113 appointments (63.10%) and the frequency of vital sign measurement differed significantly between the two clinics (68.80% at HOPES and 50.00% at CCE), p = 0.02. Conclusion: Vital signs were not consistently obtained at the HOPES and CCE Ophthalmology clinics despite diabetes and hypertension, diseases with known ophthalmologic sequelae, representing primary reasons for visit. Findings are a call to action for quality improvement measures in clinics to enforce vital sign measurement during every encounter.